Baseline characterization of the practices and use of fish feed ingredients among fish farmers in Zambia - Manyise, Timothy; Kasanga, Gregory; Ghazali, Saadiah; Yossa, Rodrigue; Rossignoli, Cristiano (2024)
This dataset presents baseline survey data from 534 fish farmers across Zambia's Luapula, Lusaka, Eastern, and Northern provinces, collected under the FASA project to inform sustainable aquaculture practices. It captures key insights on the role of local feed ingredients in fish farming, covering socioeconomic characteristics, local feed ingredient sourcing, and usage among farmers. The dataset also assesses farmers' and processors' knowledge of local ingredients in fish feed, highlighting capacity-building needs, and documents current practices, innovations, and challenges related to local ingredient use. Additionally, it explores fish farmers’ willingness to adopt local ingredient-based feeds, indicating the potential for scaling sustainable solutions. This dataset provides a resource for policymakers, researchers, and practitioners to design targeted interventions, supporting growth, productivity, and resilience in Zambia’s aquaculture sector.